THE OBJECTS OF METAPHYSICAL COGNITION: ESSENCE AND PRODUCTIVE CONTENT - Держко, І. З. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The problem of metaphysical cognition objects are analyzed, the criteria and its hierarchy are considered.